Quantifying geological processes on Mars—Results of the high resolution stereo camera (HRSC) on Mars express. (July 2015) - Jaumann, R.; Tirsch, D.; Hauber, E.; Ansan, V.; Di Achille, G.; Erkeling, G.; Fueten, F.; Head, J.; Kleinhans, M.G.; Mangold, N.; Michael, G.G.; Neukum, G.; et al.
Abstract: This review summarizes the use of High Resolution Stereo Camera (HRSC) data as an instrumental tool and its application in the analysis of geological processes and landforms on Mars during the last 10 years of operation. High-resolution digital elevations models on a local to regional scale are the unique strength of the HRSC instrument. The analysis of these data products enabled quantifying geological processes such as effusion rates of lava flows, tectonic deformation, discharge of water in channels, formation timescales of deltas, geometry of sedimentary deposits as well as estimating the age of geological units by crater size–frequency distribution measurements. Both the quantification of geological processes and the age determination allow constraining the evolution of Martian geologic activity in space and time. A second major contribution of HRSC is the discovery of episodicity in the intensity of geological processes on Mars. This has been revealed by comparative age dating of volcanic, fluvial, glacial, and lacustrine deposits. Volcanic processes on Mars have been active over more than 4 Gyr, with peak phases in all three geologic epochs, generally ceasing towards the Amazonian. Fluvial and lacustrine activity phases spread a time span from Noachian until Amazonian times, but detailed studies show that they have been interrupted by multiple and long lasting phases of quiescence. Also glacial activity shows discrete phases of enhanced intensity that may correlate with periods of increased spin-axis obliquity. The episodicity of geological processes like volcanism, erosion, and glaciation on Mars reflects close correlation between surface processes and endogenic activity as well as orbit variations and changing climate condition. Highlights: HRSC monitors the Martian surface since more than 10 years. High-resolution DTMs and image base maps are HRSC's major data contribution. HRSC data allow model age dating results of a wide range of geological units. HRSC data enable quantification of landforms, process rates, and deformation.